PROBLEMATIKA PEMAHAMAN KONSEP MATEMATIKA SISWA SEKOLAH DASAR DITINJAU DARI CARA MENGAJAR GURU - Sembiring, Reginata Thesalonika; Tarigan, Agnes Veronika Br; Siregar, Adela; Mailani, Elvi (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to examine the problems of elementary school students’ understanding of mathematical concepts in relation to teachers’ teaching strategies. The research employed a descriptive qualitative approach using structured interviews as the main data collection technique. The participants consisted of third-grade students and a mathematics teacher at SD UPT Negeri 060866 Medan Timur. Data were analyzed through stages of data reduction, data display, and conclusion drawing. The findings reveal that students’ low understanding of mathematical concepts is influenced by several interrelated factors. From the students’ perspective, the main obstacles include low learning motivation, the perception that mathematics is a difficult subject, difficulties in connecting mathematical concepts with everyday life, and limited abstract thinking abilities. From the teachers’ perspective, mathematics learning is still dominated by conventional teaching methods, limited use of learning media and concrete teaching aids, monotonous instructional strategies, and the use of language that is not aligned with students’ cognitive development. In addition, teachers rarely provide feedback or explanations regarding students’ errors in solving mathematical problems. These results indicate that students’ conceptual understanding of mathematics is closely related to the teaching strategies applied by teachers. Therefore, more interactive, contextual, and student-centered learning approaches supported by appropriate media and simple, communicative language are needed to improve students’ understanding of mathematical concepts.